Heptafluorobutyl Chloroformate-Based Sample Preparation Protocol for Nonchiral and Chiral Amino Acid Analysis by Gas Chromatography-Mass Spectrometry - Šimek, Petr; Hušek, Petr; Zahradníčková, Helena (Methods in molecular biology, 2019)
Gas chromatography (GC) is a commonly used technique in amino acid analysis (AAA). However, one of the requirements of the application of GC for AAA is a need for the polar analytes to be converted into their volatile, thermally stable derivatives. In the last two decades, alkyl chloroformates (RCFs) have become attractive derivatization reagents. The reagents react immediately with most amino acid functional groups in aqueous matrices, and the process can easily be coupled with liquid-liquid extraction of the resulting less polar derivatives into immiscible organic phase. Here we describe a simple protocol for in situ derivatization of amino acids with heptafluorobutyl chloroformate (HFBCF) followed by subsequent chiral as well as nonchiral GC/MS (mass spectrometric) analysis on a respective nonpolar fused silica and an enantioselective Chirasil-Val capillary column.
Keywords: deuterium; formiáty; Formates; izotopy uhlíku; Liquid-Liquid Extraction; Deuterium; Carbon Isotopes; lidé; Calibration; Stereoisomerism; stereoizomerie; Fluorocarbons; kalibrace; plynová chromatografie s hmotnostně spektrometrickou detekcí; extrakce kapalina-kapalina; Gas Chromatography-Mass Spectrometry; Amino Acids; fluorokarbony; aminokyseliny; Humans